2022
DOI: 10.1142/s0192415x22500744
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Traditional Chinese Medicine on Treatment of Diabetic Nephropathy and the Involved Mechanisms

Abstract: Diabetic nephropathy (DN) is a common microvascular complication of diabetes mellitus (DM), which can lead to renal failure in diabetic patients. At present, the first-line drugs for DN are mainly the renin–angiotensin system (RAS) inhibitors or angiotensin receptor blockers, and the latest approved aldosterone receptor antagonist finerenone, which delay the progression of DN to end-stage renal disease (ESRD), but the therapeutic effect is still not ideal. With a history of thousands of years, traditional Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 138 publications
0
9
0
Order By: Relevance
“…TCM had the effect of modulating gut microbiota and improving glucose metabolisms in T2DM patients and pre-clinical experiments ( Zheng et al, 2021b ). Numerous studies reviewed the efficacy and mechanisms of Chinese herbal medicine on DKD, DR, and DPN, which have been reported to be critical for diabetes in the elderly ( Lu et al, 2019 ; Ai et al, 2020 ; Chen et al, 2022b ; Liu et al, 2022 ). Whlie TCM could give full play to the advantages of multiple targets and intervene in many important mechanisms of elderly diabetes.…”
Section: Tcm Treatments Of Elderly Diabetesmentioning
confidence: 99%
“…TCM had the effect of modulating gut microbiota and improving glucose metabolisms in T2DM patients and pre-clinical experiments ( Zheng et al, 2021b ). Numerous studies reviewed the efficacy and mechanisms of Chinese herbal medicine on DKD, DR, and DPN, which have been reported to be critical for diabetes in the elderly ( Lu et al, 2019 ; Ai et al, 2020 ; Chen et al, 2022b ; Liu et al, 2022 ). Whlie TCM could give full play to the advantages of multiple targets and intervene in many important mechanisms of elderly diabetes.…”
Section: Tcm Treatments Of Elderly Diabetesmentioning
confidence: 99%
“…Although pathogenesis of DN is complex and multifactorial, inflammation, and oxidative stress have been demonstrated to have a key role to the induction and progression of DN (Winiarska et al, 2021). The results of numerous of studies emphasize the herbal medicines which have positive effects on diabetes mellitus could alleviate DN symptoms (Liu et al, 2022). It has been reported that, daily oral administration of 20 mg/kg of crocin for 8 weeks improved DN in diabetic rats.…”
Section: Effect On Urinary Systemmentioning
confidence: 99%
“…1,2 Currently, renin-angiotensin system inhibitors (RASis) and sodium-glucose cotransporter 2 inhibitors (SGLT2is) remain the primary treatment options for patients with DN. 3,4 However, patients with high levels of potassium and serum creatinine (Scr) are restricted in the use of RASis, and patients receiving SGLT2is are prone to urinary tract and genital infections. [5][6][7] Accordingly, there is an urgent clinical need to develop multitargeted therapeutic interventions for DN.…”
Section: Introductionmentioning
confidence: 99%